ANALYSIS OF EXCLUSION AND INCLUSION IN THE CONTEXT OF YOUNG UNIVERSITY - Costa, Danilo da (Revista Coleta Científica, 2019)
This work constitutes a review of the book “YOUNG UNIVERSITY: between inclusion and exclusion”, a work that belongs to the Youth, Education and Society Collection, which included the Editorial Committee composed by Geraldo Caliman (Coordinator), Célio da Cunha, Carlos Ângelo de Meneses Souza, Florence Marie Dravet, Luiz Síveres, Renato de Oliveira Brito. Its Advisory Editorial Board was: Maria Teresa Prieto (Mexico), Bernhard Fichtner (Germany), Roberto Silva (USP), Azucena Ochoa Cervantes (Mexico), Cristina Costa Lobo (Portugal). It had Geraldo Caliman and Ivar César Oliveira de Vasconcelos as organizers. It was published in Brasilia by the UNESCO Chair for Youth, Education and Society, as well as by the publisher of the Catholic University of Brasilia, in 2019.